Managerial competencies and teachers effectiveness in computer studies teaching in Ibadan metropolitan secondary schools, Oyo State, Nigeria (2016)
This study investigated managerial competencies of public secondary schools computer studies teachers in Ibadan metropolis of Oyo state, Nigeria. The descriptive survey research design of the ex-post facto type was adopted using the multi-stage sampling procedure to select one hundred and eighty-five (185) senior secondary school students and computer studies teachers in thirty-seven (37) secondary schools within Ibadan metropolis of Oyo State. Two researcher designed questionnaires titled “Computer Teachers Managerial Competencies Questionnaire (CTMCQ) 1 and 2” were used to gather data. The instruments were divided into three sections each. The validity of each instrument was ensured by experts in the Department of Educational Management, University of Ibadan, while the reliability of the instrument was established through a trial test that adopted the Crombach Alpha statistic with the split half method. The reliability coefficient of “r ” =0.710 was obtained. The data collected were analyzed using, simple descriptive statistics as frequency counts, percentages, mean, standard deviation and Pearson's Product-Moment Correlation infrential statistics. The hypothesis formulated for the study was tested and the result found significant r=0.059;p<0.05.The study affirmed that a positive correlation exists between managerial competencies and teachers' effectiveness in computer studies teaching in secondary school in Ibadan, metropolis, Oyo State, Nigeria. The study recommended that ICT teachers especially those with ten years and above work experience should be retrained so as to ensure effective ICT teaching in our educational system.